Executive leadership in Anglo-American systems - Campbell, Colin, 1943 June 10-; Wyszomirski, Margaret Jane (Pitt series in policy and institutional studies., 1991)
In this collection, eighteen distinguished scholars and practicing officials address the problems of contemporary executive leadership in the United States, Britain, Canada, and Australia. Essays focus on cabinet government; domestic, military, and economic advisers; executive agencies; and personal staff for presidents and prime ministers. Provocative comparisons between and among systems make the discussions particularly insightful.